2017
DOI: 10.1007/s00037-017-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

On vanishing of Kronecker coefficients

Abstract: Abstract. We show that the problem of deciding positivity of Kronecker coefficients is NP-hard. Previously, this problem was conjectured to be in P, just as for the Littlewood-Richardson coefficients. Our result establishes in a formal way that Kronecker coefficients are more difficult than Littlewood-Richardson coefficients, unless P = NP. We also show that there exists a #P -formula for a particular subclass of Kronecker coefficients whose positivity is NP-hard to decide. This is an evidence that, despite th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 41 publications
0
58
1
Order By: Relevance
“…so the solution to the one-body quantum marginal problem captures precisely the asymptotic support of the Kronecker coefficients [CM06, Kly06,CHM07]. We note that the problem of deciding whether gpλ, µ, νq ą 0 is known to be NP-hard [IMW17]. However since the asymptotic vanishing of Kronecker coefficients is captured by the quantum marginal problem, it has been conjectured that it should have a polynomial time algorithm and we make progress towards this question.…”
Section: Our Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…so the solution to the one-body quantum marginal problem captures precisely the asymptotic support of the Kronecker coefficients [CM06, Kly06,CHM07]. We note that the problem of deciding whether gpλ, µ, νq ą 0 is known to be NP-hard [IMW17]. However since the asymptotic vanishing of Kronecker coefficients is captured by the quantum marginal problem, it has been conjectured that it should have a polynomial time algorithm and we make progress towards this question.…”
Section: Our Settingmentioning
confidence: 99%
“…P pXq ‰ 0. In fact, it is known that even deciding the existence of highest-weight vectors is NP-hard [IMW17]. Our algorithm does not solve the membership problem via the dual description provided by Mumford's theorem.…”
Section: An Effective Version Of Mumford's Theoremmentioning
confidence: 99%
“…The actual evaluation of the LR coefficient for general Young diagrams is # P-hard [80] (# P is the analog of NP when we go from decision problems to counting problems). Recently it was found that deciding the vanishing of Kronecker coefficients is NP-hard [81]. This is an interesting contrast between central correlators in the 1-matrix problem (224) and the one-point function of central observables in the tensor model (79).…”
Section: Computational Complexity Of Central Correlators In Matrix Vementioning
confidence: 99%
“…For partitions λ, µ, ν of nd let g(λ, µ, ν) ∈ N denote the Kronecker coefficient, i.e., the multiplicity of the irreducible S nd -representation [λ] in the tensor product [µ] ⊗ [ν], where [µ] ⊗ [ν] is interpreted as an S ndrepresentation via the diagonal embedding S nd ֒→ S nd × S nd , π → (π, π). A combinatorial interpretation of g(λ, µ, ν) is known only in special cases, see [Las80,Rem89,Rem92,RW94,Ros01,BO07,Bla12,Liu14,IMW15,Hay15], and finding a general combinatorial interpretation is problem 10 in Stanley's list of positivity problems and conjectures in algebraic combinatorics [Sta00]. In geometric complexity theory the main interest is focused on rectangular Kronecker coefficients, i.e., the coefficients g(λ, n × d, n × d).…”
Section: (A) Complexity Lower Bounds Via Representation Theorymentioning
confidence: 99%